A STUDY ON LIBRARY AUTOMATION: TRENDS, CHALLENGES AND OPPORTUNITIES - Sunil Tukarama Bhosale (International Journal of Multidisciplinary Research and Studies, 2023)
This report examines chosen library automation in India's current trends, issues, and prospects. Utilizing convenience and purposeful sampling techniques, respectively. According to the survey, Dspace and Green Stone are the most widely used library automation platforms in digital libraries in India due to their interactive user interface, full-text access, and easy installation requirements. According to the survey results, valuable books, dissertations, and dissertations for scientific and research purposes were digitized most frequently. The major problems facing digital libraries in India are the lack of funding to support them, the incompatibility of digital library platforms with local languages, ​​and the lack of digital library plans, policies, and procedures. have been identified. Slow internet connections and insufficient digital collections made it difficult for users to access the digital library. The major prospects for digital libraries in India focus on document preservation for educational, cultural, historical, and governmental purposes and broader document accessibility. It is therefore proposed that digital libraries in India should have a national digital library strategy, plans, standards, and processes for digital library development in the country.